2016
DOI: 10.7150/jca.15502
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Tau has Antiproliferative effects, Represses the Expression of E6 and E7 Oncogenes, Induces Apoptosis in Cell Lines Transformed with HPV16 and Inhibits Tumor Growth In Vivo

Abstract: Interferon tau (IFN-τ) is a promising alternative antiviral and immunotherapeutic agent in a wide variety of diseases including infectious, neurodegenerative, autoimmune and cancer due to its low toxicity in comparison with other type I interferon´s. The objective of our study was established the effect of the bovine IFN-τ on human (SiHa) and murine (BMK-16/myc) cells transformed with HPV 16 and evaluates the antitumor effect in a murine tumor model HPV 16 positive. We determine that bovine IFN-τ has antiproli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Recent finding showed that IFN-τ has antiviral activity and antiproliferative effects on tumor cells. It also displays a cross-species activity in humans, mice and ruminants, and it lacks the associated toxicity of other interferons [14,15]. The fact that exogenous ovine IFN-τ has antiviral and antiproliferative effects on HPV16-positive murine and human cells is also correlated to the tumor inhibition in a cervical cancer experimental model [14], and it is linked to the activity of IFN-τ on the permissibility of tumor cells and signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent finding showed that IFN-τ has antiviral activity and antiproliferative effects on tumor cells. It also displays a cross-species activity in humans, mice and ruminants, and it lacks the associated toxicity of other interferons [14,15]. The fact that exogenous ovine IFN-τ has antiviral and antiproliferative effects on HPV16-positive murine and human cells is also correlated to the tumor inhibition in a cervical cancer experimental model [14], and it is linked to the activity of IFN-τ on the permissibility of tumor cells and signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…It also displays a cross-species activity in humans, mice and ruminants, and it lacks the associated toxicity of other interferons [14,15]. The fact that exogenous ovine IFN-τ has antiviral and antiproliferative effects on HPV16-positive murine and human cells is also correlated to the tumor inhibition in a cervical cancer experimental model [14], and it is linked to the activity of IFN-τ on the permissibility of tumor cells and signal transduction. In order to determine which downstream signaling molecules are involved in the HPV16-transformed epithelial cells, we examined the effects of the ovine interferon on the JAK-STATprotein profiling and on the phosphorylation profiling of BMK-16/myc cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alterations of protein-coding genes and signaling pathways in the initiation and progression of cervical cancer have been well recognized 36, 37. The implications of lncRNAs in cervical cancer are relative much less recognized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that viral infection triggers the activation of IFN receptor 9 (IRF9) forming a complex (ISGF3 complex) that translocates to the nucleus and binds to specific regulatory DNA sequences interfering with the transcription of many IFN-stimulated genes (ISGs). 68 Table 2 summarizes the immunologic activity of HPV proteins.…”
Section: Introductionmentioning
confidence: 99%